A novel method for examining autistic children’s comprehension of individual words produced within delayed echolalia: a proof-of-concept pilot study - Mathée-Scott, Janine; Corrigan, Grace; Lorang, Emily; Hesse, Zachary; Johnson, Jennifer; Venker, Courtney E. (Frontiers in Psychology, 2025)
Delayed echolalia, or the repetition of previously heard speech, is often observed in the expressive language of autistic children. Relatively little is known about how the production of delayed echolalia fits within the overall picture of autistic children’s language ability, including receptive language. To date, no empirical studies have tested autistic children’s comprehension of individual words within their delayed echoes. The present study aimed to establish proof-of-concept for a novel method of examining children’s comprehension of individual words that they produce in their own delayed echoes. Using natural language sampling combined with parent report, we identified instances of delayed echolalia in two young autistic children. We then employed eyegaze methods (i.e., Looking-While-Listening) to test children’s comprehension of individual target words derived from their delayed echoes. Preliminary results revealed that two autistic participants demonstrated comprehension of individual words that they produced in delayed echoes in two different carrier phrases and as single words (p’s < 0.001). These findings suggest that it is feasible to employ eyegaze methods to test autistic children’s comprehension of the individual words within their own delayed echoes.